KASUS MULTIKULTURALISME BELANDA SEBAGAI KRITIK ATAS UTOPIA MULTIKULTURALISME INDONESIA - Ibnu Nadzir (Masyarakat Indonesia, 2011)
Indonesia is failing in managing its diversity due to numerous violence actsagainst its minority groups in recent years. It is ironic because Indonesianfounding fathers have developed the ideas that Indonesia is a nation thatupholds cultural diversity. There are debates among Indonesian scholarsregarding the concept of multiculturalism as an ideal concept to solve minorityproblems in Indonesia. This paper shows that the implementation of multiculturalism in Netherlands is based on pragmatism to protect its economic interests. It also shows how multiculturalism policies in Netherlands have been facing a lot of challenges that practically unpredictable before. This paper describes the dynamics of tolerance and multiculturalism in the Netherlands. In particular, the paper shows how the ideas was developed; what kind of challenges that their values have to face. In addition, this paper also shows the relevance of Netherlands case to the issue of diversity in Indonesia today.Keywords : tolerance, multiculturalism, pluralism, diversity